صعوبات تعلم اللغة الانجليزية بالمدرسة الـــجزائرية في الطـــــــــور الابتـــــــدائي - تجاني,فردوس; همامي,خولة (My University, 2024)
This study aimed to identify the most important difficulties in learning the English language in the primary stage. To achieve this, this study relied on the descriptive approach. We conducted this study as a preliminary study of Muhammad al-Tayeb’s percussion on the wadi winds. Based on the main question of this study: Do primary school students in Algerian schools have difficulties in learning the English language and what are the reasons for this? This study relied on the following hypotheses: General hypothesis: Difficulties in learning the English language among primary school students in Algerian schools are due to several factors related to the student’s own surroundings and others external to them. Sub-hypotheses: 1. The difficulties in learning the English language among primary school students in Algerian schools are due to the student’s family environment. 2. -The difficulties of learning the English language among primary school students in Algerian schools are due to the student’s school environment. 3. -The difficulties of learning the English language among primary school students in Algerian schools are due to the student himself and his perceptions of this language.The study sample consisted of 501 male and female students in the third and fourth stages of primary school for the academic year 2023/2024 AD, which was represented by the intentional purposive sample type. To collect data, use the questionnaire tool; It included 26 questions and was divided into three axes that answer the hypotheses: This study reached a number of results, the most important of which are: هدف هذه الدراسة إلى التعر على أهم صعوبات تعلم اللغة اإشنجليزية في طور اإشبتدائي، ولتحقيق ذلك تم الاعتماد في هذه الدراسة على المنهج ال وصفي. حيث بمنا بإجراء هذه الدراسة بإبتدائية لقرع محمد الطيب بالرياح الوادي. انطلابا من التساؤل الرئيسي لهذه الدراسة: هدل لدى تلاميذ الطور الإبتدائي بالمدرسة الجزائریة صعوبات في تعلم اللغة الإنجليزیة وإلى ماذا ترجع هدذه الاخيرة؟ حيث اعتمدت هذه الدراسة على الفرضيات التالية:  الفرضية العامة: ترجع صعوبات تعلم اللغة اإشنجليزية لدى تلاميذ الطور اإشبتدائي بالمدرسة الجزائرية إلى عدة عوامل مرتلطة بمحيط التلميذ نفسه وأخرى خارجية.  الفرضيات الفرعية: 1. ترجع صعوبات تعلم اللغة اإشنجليزية لدى تلاميذ الطور الابتدائي بالمدرسة الجزائرية إلى المحيط الأسري للتلميذ. 2. -ترجع صعوبات تعلم اللغة اإشنجليزية لدى تلاميذ الطور اإشبتدائي بالمدرسة الجزائرية إلى المحيط المدرسي للتلميذ. 3. -ترجع صعوبات تعلم اللغة اإشنجليزية لدى تلاميذ الطور اإشبتدائي بالمدرسة الجزائرية إلى التلميذ نفسه وتصوراته نحو هذه اللغة. وبد تألف عينة الدراسة من 501 تلميذ وتلميذة في مرحلتي الثالثة والرابعة إبتدائي للموسم الدراسي 8082/8082م والمتمثل في نوع العينة القصدية العمدية. ولجمع الليانات استخدام أداة اإشستليان؛ حيث شمل 82 سؤالا ا والمقسم إلى ثلاث محاور تجيب على الفرضيات؛ حيث توصل هذه الدراسة إلى جملة من النتائج أهمها:  يمكن أن تلعب الأسرة دورا مهما في تحفيز الأبناء وتوفير فرص الممارسة من خلال الدعم الأسري والعكس.  ينعكس المحيط المدرسي ويؤثر سللا أو إيجابا من خلال المعلم وأسلوبه مع التلاميذ.
Keywords: صعوبات التعلم; اللغة الانجليزية; الطو; ر الابتدائي; learning difficulties; English language; Primary stage